A Community-Based Approach to Biospecimen Collection Among Pacific Islanders. Issue 1 (January 2020) - Kwan, Patchareeya Pumpuang; Sabado-Liwag, Melanie; Tan, Nasya; Pike, James Russell; Custodio, Harold; LaBreche, Amanda; Fex, Cleo; May Tui'one, Vanessa; Pang, Jane Ka'ala; Pang, Victor Kaiwi; Sablan-Santos, Lola; Toilolo, Tupou; et al.
This study tested the feasibility of collecting saliva samples from Pacific Islanders (PIs) via a community-based participatory research approach. Collection of saliva samples were conducted by trained and trusted PI community leaders at various partner sites. A total of 214 saliva samples were donated by PIs living in Southern California, more than half of whom were females between the ages of 18 and 35 years. Donors indicated that they donated because they wanted to help science and their community. A majority of donors reported a very positive experience with the donation process and were willing to donate saliva and hair samples in the future. The positive findings of this article highlight the importance of community input and participation.